Creating Markets in Fiji : Overview and Summary of Key Findings from Sector Deep Dives - Country Private Sector Diagnostic - International Finance Corporation (World Bank, Washington, DC, 2022)
This Country Private Sector Diagnostic (CPSD) comes at a challenging yet opportune juncture for Fiji to rebuild a more diverse and resilient economy amid the lingering impacts of COVID-19. Fiji recorded its strongest period of gross domestic product (GDP) growth (since achieving independence in 1970) in the decade leading up to COVID-19, underpinned by rising productivity and investment, improved political stability, and a booming tourism sector. However, the shocks of COVID-19 and a series of natural disasters, Tropical Cyclone (TC) Harold and TC Yasa, have been devastating for Fiji’s economy, bringing widespread production disruptions and job losses. The increasing frequency of these weather events has also complicated Fiji’s economic development strategy and plans. Fiji’s real GDP declined by 15.2 percent in 2020 and is estimated to have contracted a further 4.0 percent in 2021, with the long-term ramifications of the COVID-19 pandemic on the economy yet to be fully seen. These shocks have also exacerbated some of Fiji’s long-standing structural vulnerabilities, including the economy being vulnerable to repeated climate-related shocks, its lack of sectoral diversification, and sluggish private sector job growth (particularly among youth and women). In this context, the CPSD approach for Fiji to ‘build back better’ revolves around four key interrelated pillars: (1) unlocking new sectoral sources of growth beyond tourism; (2) strengthening economic and climate resilience; (3) leveraging Fiji’s potential as an economic hub in the Pacific region; and (4) creating inclusive employment opportunities.